Procurement. Issue 3 (7th May 2019) - Moss, Robert John; Batista, Aida; Makridaki, Despina; Süle, András; Kohl, Stephanie
Abstract : EAHP's position paper advocates for the involvement of hospital pharmacists in procurement. The immediate concern of any hospital pharmacist is to ensure that every patient within the hospital receives the medications needed. For this reason, hospital pharmacists have a direct stake in the efficient functioning of the medicines' supply chain. The position touches on pharmaceutical tendering which is a complex process that involves different stakeholders and steps that are regulated at national level leading to diverse solutions in the different European countries. In addition, these processes are guided by publications of other international actors such as the World Health Organisation (WHO) and the Organisation for Economic Co-operation and Development (OECD). The second part focuses on the role of hospital pharmacists in procurement which due to their knowledge and skills are specialists in the field of all medicines' procurement. Hospital pharmacists should lead in all phases of the procurement processes and practices to ensure the continuity of the supply of cost-effective and quality medicines to patients.